A comparison study between V-SBA-15 and V-KIT-6 catalysts for selective oxidation of diphenylmethane. (4th July 2019) - Santhanaraj, D.; Suresh, C.; Selvamani, A.; Shanthi, K.
Abstract : Vanadium incorporated mesoporous SBA-15 and KIT-6 catalysts were prepared by a direct hydrothermal method under mild acidic reaction conditions. Abstract : Vanadium incorporated mesoporous SBA-15 and KIT-6 catalysts were prepared by a direct hydrothermal method under mild acidic reaction conditions. The structural features of the catalysts have been thoroughly investigated by using various characterization techniques including N2 -physisorption, X-ray diffraction, 51 V NMR spectroscopy, Raman spectroscopy, H2 -TPR, and XPS. The characterization results revealed that under hydrated conditions, the incorporated vanadium was highly dispersed on the surface of SBA-15 and KIT-6 catalysts with octahedral coordination. However, the various spectral analyses manifest that the local environment of vanadium is entirely different for SBA-15 and KIT-6 supports. The influence of the supports and their catalytic activity for the diphenylmethane oxidation reaction are investigated. The efficiency of the catalysts was compared in terms of a constant level of vanadium loading on both the catalysts, and it was observed that the V-KIT-6 catalyst exhibited better catalytic activity than V-SBA-15. The enhanced activity of the V-KIT-6 catalyst was mainly attributed to the presence of a large portion of vanadium on the external walls with the V 5+ oxidation state. The deactivation study was performed on both catalysts and it was found that both catalysts exhibited a similar level of conversion and selectivity under identical experimental conditions. In addition, the catalytic activity was directly correlated with various characterization results.